Использование метода спиновых зондов для оценки цитотоксичности углеродных нанотрубок - Картель, Н.Т.; Грищенко, В.И.; Черных, В.П.; Иванов, Л.В.; Нардид, О.A.; Семенцов, Ю.И.; Приходько, Г.П.; Коваленко, С.Н.; Губин, Ю.И.; Репина, С.В. (Видавничий дім "Академперіодика" НАН України, 2009)
Для вивчення механiзмiв цитотоксичностi вуглецевих нанотрубок (ВНТ) застосовано модификацiї методу спiнових зондiв. Показано, що пошкодження мембран еритроцитiв пiд дiєю ВНТ розвивається у часi, зокрема, при введеннi суспензiї ВНТ (200 мкг/мл) через 2 доби експозицiї зразкiв (6 °C) кiлькiсть пошкоджених еритроцитiв становила 25%. Експозицiя гомогенату печiнки з ВНТ протягом 4 год при 0 °C призводить до значного зниження мiтохондрiальної активностi (iнгiбуванню ланцюга передачi електронiв у мiтохондрiях). Отриманi данi показують, що цитотоксичнiсть, обумовлена дiєю ВНТ, пов’язана не тiльки зi змiною мембранних структур клiтин, а й з впливом на їхнi функцiональнi властивостi. To study the mechanisms of cytotoxicity of carbon nanotubes (CNT), we have applied the modified method of spin labels. It is shown that the damage of erythrocytes membranes under the influence of CNT develops in time. In particular, under the introduction of a CNT suspension at a concentration from 10 to 200 mkg/ml during 2 days at a temperature of 6 °C, the amount of damaged erythrocytes was 25%. The exposition of liver homogenate with CNT for 4 h at a temperature of 0 °C leads to a considerable decrease of the mitochondrial activity (to the inhibition of a chain of transfer of electrons in mitochondria). The obtained data show that the cytotoxicity caused by the action of CNT is connected not only with a change of membrane structures of cells, but also influence their functional properties.